DEVELOPMENT OF AN ATTITUDE MODEL BASED ON VALUES FOR ONE'S OWN HEALTH - Valentyna Kupchyshyna; Mariana Levko; Liudmyla Matsuk; Tetiana Kotyk; Olena Homoniuk (Journal of Physical Education)
ABSTRACT The article presents the basic elements of our model of development of value-based attitude to person’s health among representatives of students of higher educational institutions, using students studying for the specialty “Civil Security” as an example. The effectiveness and efficiency of this model of the bull was tested using a comprehensive experimental and pedagogical method, the results of which are also given. These studies will allow representatives of higher educational institutions of teaching staff and other interested parties to quickly form an effective system of maintaining health among students of physical culture As a result of the study, it was found that the use of this model and pedagogical conditions is a favorable factor in the process of forming a value attitude to health among future civil security specialists.